Association between meteorological factors, air pollutants and daily hospitalizations of coronary heart disease in rural areas of southern Xinjiang, China - Han, Xueying; Ma, Rulin; He, Jia; Yang, Bo; Chen, Silin; Wu, Xuelian; Muhetaer, Dilimulati; Ma, Lanqing; Shen, Shijie; Li, Xiaoxue; Zuo, Pengxiang; Guo, Heng (Frontiers in Public Health, 2025)
IntroductionMeteorological factors and air pollutants are two important factors affecting hospitalisation for coronary heart disease. This study aims to investigate the effects of meteorological factors and air pollutants on the risk of coronary heart disease hospitalisation and their interactions in rural areas with heavy particulate matter pollution at the edge of the desert in southern Xinjiang.MethodsIn this study, patients with coronary heart disease who were hospitalized in Tangyi Town, Tumushuke City, Xinjiang Province, were selected as the study subjects, and the lagged effects of meteorological factors and air pollutants on the risk of coronary heart disease hospitalisation and their interactions were analysed by combining the distributional lag nonlinear model and the quasi-Poisson regression model.ResultsThe results showed that the associations between meteorological factors and air pollutant concentrations with the risk of coronary heart disease hospitalisation both showed non-linear and lagged effects. There was an antagonistic effect between mean daily temperature and PM2.5 and PM10 on the effect of coronary heart disease hospitalisation, with RERIs of −0.73 (95% CI: −2.63, −0.04), and −1.14 (95% CI: −1.93, −0.60), respectively. The relative risk of coronary heart disease hospitalisation in the low-temperature, high PM10 concentration environment was 1.53 (95% CI: 1.09, 2.13). The risk of hospitalization for coronary heart disease is increased by 30 and 19% in environments with low humidity and high PM2.5 and PM10 concentrations, respectively. There are also interactions between particulate matter and gaseous pollutants and between different gaseous pollutants.DiscussionThis study suggests the need to necessity of management of multiple air pollutants and response to climate change, as well as the importance of implementing targeted preventive and control measures by the relevant authorities in according to meteorological and air pollution conditions, which can effectively reduce the hospitalization rate of patients with coronary heart disease.